2018
DOI: 10.1177/0049124118769114
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Coding: A Comparison of Hand-Coding and Three Types of Computer-Assisted Text Analysis Methods

Abstract: Advances in computer science and computational linguistics have yielded new, and faster, computational approaches to structuring and analyzing textual data. These approaches perform well on tasks like information extraction, but their ability to identify complex, socially-constructed, and unsettled theoretical concepts -a central goal of sociological content analysis -has not been tested. To fill this gap, we compare the results produced by three common computer-assisted approaches -dictionary, supervised mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 51 publications
1
94
0
1
Order By: Relevance
“…The coding methods used were hand coding, machine learning, or a combination of the two. Compared with hand coding, machine learning can rapidly code large amounts of data; however, hand coding undertaken by humans may more accurately discriminate the complexities and subtleties of language [54]. Although hand coding can be subject to individual bias, the development of codes grounded in literature and achieving acceptable levels of inter-rater reliability can assist to reduce this [55].…”
Section: Discussionmentioning
confidence: 99%
“…The coding methods used were hand coding, machine learning, or a combination of the two. Compared with hand coding, machine learning can rapidly code large amounts of data; however, hand coding undertaken by humans may more accurately discriminate the complexities and subtleties of language [54]. Although hand coding can be subject to individual bias, the development of codes grounded in literature and achieving acceptable levels of inter-rater reliability can assist to reduce this [55].…”
Section: Discussionmentioning
confidence: 99%
“…Like topic modeling, content analysis shows an extremely meaningful trend with a positive slope. For more details about content analysis, refer to [139]- [144].…”
Section: The Second Category Represented Common Research Paperrelatedmentioning
confidence: 99%
“…The first, most general dimension for evaluating any algorithm is determining the correctness of its results. There are many different measures for evaluating labeling or classification algorithms (Nelson et al 2018). In general, commercial labeling systems present users with only predicted positive labels (e.g., "there are cats in this photograph") and not predicted negative labels (e.g., "there are no children").…”
Section: Evaluating Gcvmentioning
confidence: 99%
“…The overall accuracy of an algorithm such as GCV is not the only important measure, however. As Nelson et al (2018) showed, sometimes the measures of correctness for individual categories and labels are more important for sociological analysis and can lead to further insights about the data. We test this with gender.…”
Section: Bias In Identificationmentioning
confidence: 99%